Pengaruh Profitabilitas, Tax Incentive Dan Corporate Social Responsibility Terhadap Penghindaran Pajak (Studi Empiris pada Perusahaan Sub Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2024) - Inggi Rengganis; Sri Purwaningsih (Annusfy : Journal of Multidisciplinary Research, 2026)
Tax avoidance is a tax avoidance effort that is carried out legally for individual and corporate taxpayers without conflicting with existing tax regulations by exploiting the weaknesses (grey area) contained in the Law and Taxation Regulations in order to produce a lower tax amount. This study aims to examine the effect of profitability, tax incentives, and corporate social responsibility on tax avoidance. Profitability is a ratio that indicates a company’s ability to generate profits. Tax incentives are facilities in the form of reduced tax rates provided by the government. Corporate Social Responsibility (CSR) is a company’s commitment to participating in sustainable economic development to improve the quality of life and the environment in a beneficial way. The population in this study consists of companies in the basic materials sub sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sampling technique used is purposive sampling, resulting in a total sample of 14 companies. The data analysis method uses Structural Equation Modeling (SEM) with Smart PLS Version 4.0.